Research on growth factors in periodontology. Issue 1 (February 2015) - Smith, Patricio C.; Martínez, Constanza; Cáceres, Mónica; Martínez, Jorge
Abstract: Growth factors play critical roles in periodontal repair through the regulation of cell behavior. Many of the cell responses regulated by these proteins include cell adhesion, migration, proliferation and differentiation. Periodontal regeneration involves an organized response of different cells, tissues and growth factors implicated in the coordination of these events. However, periodontal tissue reconstruction is an extremely difficult task. Multiple studies have been performed to understand the specific role of growth factors in periodontal wound healing. In the present review we analyze the evidence that supports the roles of growth factors in periodontal wound healing and regeneration.